The impact of diet liberalization on bowel preparation for colonoscopy - Walter, James; Francis, Gloria; Matro, Rebecca; Kedika, Ramalinga; Grosso, Rachael; Keith, Scott W.; Kastenberg, David (Endoscopy International Open, 2017)
Background and study aims Dietary restrictions are integral to colonoscopy preparation and impact patient satisfaction. Utilizing split-dose, lower-volume polyethylene glycol 3350-electrolyte solution (PEG-ELS), this study compared colon preparation adequacy of a low-residue diet to clear liquids using a validated grading scale. Patients and methods This was a prospective, randomized, single-blinded, single-center non-inferiority study evaluating diet the day prior to outpatient colonoscopy. Subjects were randomized to a Low-Residue diet for breakfast and lunch, or Clears only. All subjects received split dose PEG-ELS. The primary endpoint was preparation adequacy using the Boston Bowel Preparation Scale (BBPS), with adequate defined as a score > 5. Secondary endpoints included mean BBPS scores for the entire colon and individual segments, satisfaction, adverse events, polyp and adenoma detection rates, and impact on sleep and daily activities.Results Final analysis included 140 subjects, 72 assigned to Clears and 68 to Low-Residue. The Low-Residue diet was non-inferior to Clears (risk difference = – 5.08 %, P = 0.04) after adjusting for age. Mean colon cleansing scores were not significantly different overall and for individual colonic segments. Satisfaction with the Low-Residue diet was significantly greater (P = 0.01). The adenoma detection rate was not statistically significantly different between study groups, but the number of adenomas detected was significantly greater with Clears (P = 0.01). Adverse events and impact on sleep and activities did not differ significantly between diet arms. Conclusions A low-residue diet for breakfast and lunch the day prior to colonoscopy was non-inferior to clear liquids alone for achieving adequate colon cleansing when using split dose PEG-ELS.